Building digital estates: multiscreening, technology management and ephemeral television - Evans, Elizabeth; Coughlan, Tim; Shipp, Victoria (Sage, 2017)
The UK television industry has increasingly integrated multiple screen technologies into multiplatform ‘digital estates’. Such ‘digital estates’ also emerge in domestic contexts. The complex, but mundane and ephemeral nature of these domestic ‘digital estates’, requires new methodologies for understanding how they operate within the daily lives of audiences. This article uses an innovative, technologically enabled observation methodology to explore how domestic ‘digital estates’ are managed. Dominant throughout our sample is the use of multiple screen technologies to create deliberately passive and ephemeral experiences, highlighting the need to recognise and interrogate the place of ‘passivity’ within televisual and digital screen experiences.